Integrasi Ibadah dan Kesehatan: Edukasi Manfaat Wudhu dan Sholat melalui Buku Saku pada Ibu-ibu Majelis Ta’lim - Octarya, Zona; Yenti, Elvi; Mardhotillah, Mardhotillah (Jurnal Pengabdian UntukMu NegeRI, 2026)
The community generally still perceives the movements in wudu and prayer merely as ritual worship activities, so many people are not yet aware that these practices also have important health benefits. In fact, the movements in wudu and prayer not only carry religious value but also provide significant health benefits and influence biochemical reactions in the body. This community service activity aimed to provide understanding to the women of the Asy-Syakur Mosque Majelis Ta’lim, Lembah Sari, Rumbai Timur, Pekanbaru, regarding the health benefits of wudu and prayer movements through pocket book–based training. The methods used in this program included lectures, interactive discussions, and hands-on practice of wudu and prayer according to the Sunnah, based on the references Sifat Shalat Nabi and Mukjizat Gerakan Shalat. Evaluation was carried out using pretests and posttests. The results showed an increase in participants’ understanding of the health benefits of wudu and prayer; after the program, more than 90% of participants understood the correct procedure of wudu and the prayer movements in accordance with the Sunnah. This community service activity had a positive impact on increasing religious awareness while simultaneously promoting physical and spiritual health..